Gaps in stone walls - Neufeld, John. (New York : Atheneum Books for Young Readers, 1996)
Twelve-year-old Merry Skiffe, who lives on Martha's Vineyard in the 1880s, runs away from home because she is suspected of having committed a murder.
Includes partial bibliography. (pages 184-186).
Keywords: Murder -- Juvenile fiction; Deaf people -- Juvenile fiction; People with disabilities -- Juvenile fiction; Murder -- Fiction; Runaways -- Fiction; Deaf people -- Fiction; People with disabilities -- Fiction